2002
DOI: 10.1002/gps.739
|View full text |Cite
|
Sign up to set email alerts
|

Qigong as a psychosocial intervention for depressed elderly with chronic physical illnesses

Abstract: Literature uncovers that depression is common in elderly people. The problem is more serious in elderly with chronic physical illnesses. Although the relationship between physical problems and depression is well documented, the underlying mechanism is basically unknown. This article proposed after a comprehensive literature review that depression in elderly with chronic physical illnesses results from disability and a reduction in psychosocial resources. If depression is left untreated, suicide may be a conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
92
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 31 publications
5
92
0
1
Order By: Relevance
“…The findings supported Tsang's model of the psychosocial effects of qigong on elderly with depression (Tsang et al, 2002). However, the causal relationship among the variables remains to be empirically verified.…”
Section: Discussionsupporting
confidence: 61%
“…The findings supported Tsang's model of the psychosocial effects of qigong on elderly with depression (Tsang et al, 2002). However, the causal relationship among the variables remains to be empirically verified.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies have analyzed the impact of qigong on social function and also reported that qigong improved this parameter. 12,28 On other SF-36 quality-of-life subscales, as well as sleep and vital sign measurements, there were no significant changes between groups over the course of the study. Other investigations have reported that qigong practice decreased blood pressure and pulse rate.…”
Section: Discussionmentioning
confidence: 87%
“…These are chronic health problems that can cause more disability and/or pain when compared with impaired visual and auditory acuity. These disabilities may lead to dependence and also have influenced the social and living skills, and self-efficacy of the participants, thus leading to depression and lesser life satisfaction (Tsang et al, 2002;Copsey Spring et al, 2007;Katon et al, 2007).…”
Section: Discussionmentioning
confidence: 98%